Mapping the Evolution of Green HRM in Universities: A Bibliometric Analysis of Trends, Collaborations, and Emerging Themes - Dhungana, Dipendra (NPRC Journal of Multidisciplinary Research, 2025)
Background: Green Human Resource Management (GHRM) is an emerging interdisciplinary field, integrating sustainability principles into organizational practice. As institutions of research and innovation, universities play a pivotal role in GHRM development, yet detailed analysis of recent trends, collaborations, and thematic focuses is lacking. Objective: The aim of this study is to investigate the evolution of GHRM research in universities from 2020 to 2024, covering publication trends, major contributors, collaboration networks, and prevailing research themes in order to map the current landscape and future direction. Methods: Lens.org was utilized to conduct a bibliometric study, searching 609 Open Access (Gold) journal articles using the search term "Green human resource management" AND University. Data were analyzed for publication trends, authors' citations, co-authorship networks, journal visibility, and keyword co-occurrence using software like VOSviewer. Findings: Annual publications peaked in 2022 (n=171), reflecting heightened global sustainability initiatives, with declines in 2023–2024 signaling market saturation. Leading journals (e.g., Journal of Environmental Management, Sustainability) and authors (e.g., Abdullah Al Mamun, Katalin Szabó) revealed interdisciplinary collaboration, most prominently in Asia and Europe. Keyword analysis revealed encompassing themes such as employee green behavior, circular economy, and sector-specific applications (e.g., hospitality, healthcare). Conclusion: GHRM research is rapidly expanding, driven by sustainability agendas and institutional policies globally. Regional asymmetries and fragmented networks of collaboration, nevertheless, indicate the scope for stronger cross-border collaborations and action research. Novelty: This article conducts the first joint bibliometric analysis of GHRM in universities, leveraging Open Access data to uncover accessibility gaps and interdisciplinary intersections, and reveal underdeveloped niches like green self-efficacy and proactive pro-environmental behavior.